Reversible Mydriasis of Sudden Onset: Think Before You Act - Garcia Castro, Jesús; Díaz de Terán, Javier (The Journal of emergency medicine, 2021)
The presence of abrupt anisocoria in clinical examination usually leads to the performance of urgent neuroimaging studies to exclude intracranial hemorrhage, although unilateral mydriasis might be the result of other benign etiologies. In this work, we report an illustrative case of a patient presenting with sudden-onset anisocoria while receiving ipratropium bromide nebulization in the emergency department to treat acute asthma. No other abnormalities were found on neurological examination and the computed tomography scan was normal. As a muscarinic antagonist, ipratropium bromide can produce mydriasis if accidentally instilled on one eye, thus leading to the suspicion of pharmacologic mydriasis. The pupils became isocoric after the discontinuation of the drug. A careful neurological examination and the history of treatment with mydriatic drugs might avoid unnecessary tests and radiation exposure.